Failure of low-dose heparin to improve efficacy of peroperative intermittent calf compression in preventing postoperative deep vein thrombosis. - Roberts, V C (1975)
The possible benefits of adding a low-dose heparin regimen to the technique of peroperative intermittent calf compression for preventing deep vein thrombosis (D.V.T.) were assessed in a randomized trial in 84 surgical patients. The efficacy of peroperative intermittent calf compression was not enhanced by a low-dose heparin regimen, but neither was it worsened. Age, weight, duration, operation, and malignant disease did not affect the relative effectiveness of the two regimens of prophylaxis. The results confirmed that venous stasis is the principal cause of D.V.T.